Transistor‐Like Modulation of Gold Nanoparticle Film Conductivity Using Hydrophobic Ions. Issue 5 (16th April 2014) - Chow, Edith; Raguse, Burkhard; Müller, Karl‐H.; Wieczorek, Lech; Cooper, James S.; Hubble, Lee J.; Webster, Melissa S.
<x xml:space="preserve">Abstract</x> A general method to modulate the source‐drain resistance of a functionalized metal nanoparticle film in an aqueous electrolyte solution, through application of a gate potential in combination with hydrophobic gate ions is described. The results have implications for the development of ionic logic systems as well for improving the sensitivity of chemical sensors by several orders of magnitude. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>